2016
DOI: 10.1186/s13021-016-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calculation methods for estimating annual carbon stock change in German forests under forest management in the German greenhouse gas inventory

Abstract: BackgroundThe German greenhouse gas inventory in the land use change sector strongly depends on national forest inventory data. As these data were collected periodically 1987, 2002, 2008 and 2012, the time series on emissions show several “jumps” due to biomass stock change, especially between 2001 and 2002 and between 2007 and 2008 while within the periods the emissions seem to be constant due to the application of periodical average emission factors. This does not reflect inter-annual variability in the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Results from the German forest inventory revealed that deadwood pools increased by 0.06 Mg C ha -1 a -1 during 1990-2008 (Dunger et al, 2016). This suggests, that changes in the deadwood pool could not explain the differences between both methods.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…Results from the German forest inventory revealed that deadwood pools increased by 0.06 Mg C ha -1 a -1 during 1990-2008 (Dunger et al, 2016). This suggests, that changes in the deadwood pool could not explain the differences between both methods.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…2.3. Estimation of carbon stocks 2.3.1 Above-and below-ground living tree biomass First the above-and below-ground living tree biomass is estimated by means of biomass functions derived from the data of the National Forest Inventory, described in Röhling et al (2016). Within the integrated model for estimating the above-ground biomass on single tree level the predictors DBH, height and the diameter in one third of the tree height are used.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Uganda reports on CO 2 only although is contemplating to start estimating CH 4 and N 2 O emissions from biomass burning in the inventory using Global Food and Agriculture Statistics of FAO (FAOSTAT) data. In terms of pools, Germany reports on positive (source) and negative (sink) CO 2 emission removals from mineral and organic soils (Prechtel et al 2009;Röhling et al 2016), aboveground biomass (AGB) and belowground biomass (BGB) (Röhling et al 2016;Tiemeyer et al 2020a, b), litter, and deadwood (Dunger et al 2012)…”
Section: Scopementioning
confidence: 99%
“…Mean annual emissions are estimated as the ratio of the difference in stock estimates at two points in time and the number of intervening years (McRoberts et al 2018). Germany developed her own unique sampling strategy that uses similar principles to the IPCC's stock-difference method (Röhling et al 2016). Stock change estimations in Germany are carried out using the continuous forest inventory (Wellbrock et al, 2017) method which ultimately relates to IPCC's stockdifference method (IPCC 2006, 2 Vol 4, Ch 2, Eq.…”
Section: Estimation Of Carbon Change In Germany's Biomass Poolsmentioning
confidence: 99%